Analysis of the Acceptance Level of E-Wallet as a Non-Cash Payment Method among Indonesian Students - Juan Galang; Haikal Ramdhan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
This research delves into the adoption of e-wallets, specifically Shopee Pay, among Indonesian students in the digital economic era. The study aims to analyze students' acceptance levels of e-wallets as a non-cash payment method, motivated by the rapid advancement in information and communication technology and the emerging need for efficient and secure financial transactions. Employing a survey-based approach, the research focuses on students' perceptions regarding the ease of use, usefulness, and perceived risks of e-wallets.The findings reveal a predominantly positive perception among students towards e-wallets. A significant majority of respondents acknowledge the ease and benefits of non-cash transactions, indicating effective implementation of this technology. Moreover, the low risk perception underscores a sense of security among students in using e-wallets. Conclusively, e-wallets, particularly Shopee Pay, demonstrate considerable potential as a favored non-cash payment method among Indonesian students. This widespread acceptance can catalyze the growth of the digital payment ecosystem, propelling Indonesia's digital financial transformation. The study offers valuable insights into consumer preferences and behaviors concerning e-wallets, aiding fintech companies and financial institutions in enhancing digital payment services. The adoption of e-wallets by students not only boosts transaction efficiency but also contributes to the expansion of Indonesia's digital economy. These findings provide a foundation for further research into the acceptance of non-cash payment technologies in Indonesian society.